the place of babies in confronting adult-centrism: possibilities based on cartography and the philosophy of difference - vanin chaves, vanessa; bertoncini vicenzi, vinicius (childhood & philosophy, 2024)
This article is an essay to think about pedagogical practices with babies from a philosophy of childhood that is not shaped by adult-centric discourses. The debate around coping with adultcentrism has historically focused more on children than on babies. This article seeks to raise questions about thinking this age not from the visible labels, marked by a chronological view, but from a conception that allows one to perceive their actions and their developments from their imminent difference. Subdivided into sections that involve the perspective of the child-becoming of Gilles Deleuze and the conception of cartography of Gabriela Tebet, this article allows us to imagine other scenarios for childhood and a possibility of perceiving babies as protagonists. Thus, we seek to understand new perceptions with babies, seeking to rethink the relationship we have with them. Thinking babies from a becoming-child discourse is to study the networks that constitute them in order to understand the movements between the immanence and organizational plans of babies. It is not to study the individual, as it is not just to study any objective truth given a priori. Thus, the researcher processes the new spaces and walks paths in search of knowing who these subjects are that arise as a form of rupture. We propose to question the ideas that involve childhood exploring the modern pedagogical ideals that marked it, in the pursuit of experiencing childhood and in the understanding of a pedagogical practice with babies capable of being a time of joy and intensity of life.